2020
DOI: 10.1002/aqc.3330
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of whale shark (Rhincodon typus) off northern Peru based on habitat suitability

Abstract: 1. In the south-eastern Pacific Ocean, few studies of whale sharks (Rhincodon typus) exist. In Peru, the northern coast has been identified as the area with the highest presence of whale sharks, yet their ecology in this area is poorly defined.2. This study predicts the spatial distribution of whale sharks off coastal northern Peru (03 00 0 S-04 30 0 S) during La Niña and El Niño seasonal conditions, utilizing maximum entropy modelling. Between 2009 and 2018 (except for 2011), 347 whale sharks were geo-referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…The observed climate differences between seasons in the three aggregation sites evidenced the effect of environmental factors on habitat suitability (González‐Pestana et al ., 2020). For instance, in BLA the relative density of whale sharks was related to deep waters and steeper slopes, higher CHLO a concentration and lower SST.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed climate differences between seasons in the three aggregation sites evidenced the effect of environmental factors on habitat suitability (González‐Pestana et al ., 2020). For instance, in BLA the relative density of whale sharks was related to deep waters and steeper slopes, higher CHLO a concentration and lower SST.…”
Section: Discussionmentioning
confidence: 99%
“…These records were obtained during multiple scientific or tourist surveys, in which a standardization according to the sampling effort was not possible, thus the records of occurrence were driven by the different sampling efforts in known distribution areas. However, the combination of records, along with environmental factors, were useful for the description of the habitat suitability of whale sharks as it has been proved in other studies (González‐Pestana et al ., 2020; Melo‐Merino et al ., 2020). Once the database of historical occurrences was generated, the sightings were processed with a single sightings record considered for every 1 km 2 to decrease spatial autocorrelation (Radosavljevic & Anderson, 2014) which was included in a geographic information system QGIS v.3.4.4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary productivity is also an important factor that affects shark distribution and abundance (MacKenzie et al, 2019). Many studies have widely demonstrated the relationship between the primary productivity and fisheries catch (Pauly and Christensen, 1995;Watson et al, 2014), and primary productivity variability is significantly and positively correlated to the mean trophic level of catches (Conti and Scardi, 2010); therefore, the primary productivity is used in most SDMs (Gonzalez-Pestana et al, 2020;Chan et al, 2021). Other environmental variables like depth, dissolved oxygen, salinity, and offshore distance are often used in the study of marine shark distribution (Sequeira et al, 2014;Meyers et al, 2017;Chan et al, 2021;Pottie et al, 2021;Gonzaĺez-Andreś et al, 2021).…”
Section: Data Sources and Preparationmentioning
confidence: 99%
“…The potential distribution of the whale shark (R. typus) was the most extensive in the present study area. The whale shark is a filter-feeding shark with global distribution in tropical and warm temperate regions that fed on zooplankton (Pierce and Norman, 2016;Gonzalez-Pestana et al, 2020). The scalloped hammerhead (S. lewini) is also distributed in warm temperate and tropical seas and frequently occurs in the southern South China Sea and the southern Gulf of Mexico.…”
Section: Distribution Patterns and Diversity Hotspots For Sharksmentioning
confidence: 99%